Dual Effects of Chinese Herbal Medicines on Angiogenesis in Cancer and Ischemic Stroke Treatments: Role of HIF-1 Network - Hong, Ming; Shi, Honglian; Wang, Ning; Tan, Hor-Yue; Wang, Qi; Feng, Yibin (Frontiers in Pharmacology, 2019)
Hypoxia-inducible factor-1 (HIF-1)–induced angiogenesis has been involved in numerous pathological conditions, and it may be harmful or beneficial depending on the types of diseases. Exploration on angiogenesis has sparked hopes in providing novel therapeutic approaches on multiple diseases with high mortality rates, such as cancer and ischemic stroke. The HIF-1 pathway is considered to be a major regulator of angiogenesis. HIF-1 seems to be involved in the vascular formation process by synergistic correlations with other proangiogenic factors in cancer and cerebrovascular disease. The regulation of HIF-1–dependent angiogenesis is related to the modulation of HIF-1 bioactivity by regulating HIF-1α transcription or protein translation, HIF-1α DNA binding, HIF-1α and HIF-1α dimerization, and HIF-1 degradation. Traditional Chinese herbal medicines have a long history of clinical use in both cancer and stroke treatments in Asia. Growing evidence has demonstrated potential proangiogenic benefits of Chinese herbal medicines in ischemic stroke, whereas tumor angiogenesis could be inhibited by the active components in Chinese herbal medicines. The objective of this review is to provide comprehensive insight on the effects of Chinese herbal medicines on angiogenesis by regulating HIF-1 pathways in both cancer and ischemic stroke.